2014
DOI: 10.1038/ng.3020
|View full text |Cite
|
Sign up to set email alerts
|

A three-stage genome-wide association study identifies a susceptibility locus for late radiotherapy toxicity at 2q24.1

Abstract: There is increasing evidence supporting the role of genetic variants in the development of radiation-induced toxicity. However, previous candidate gene association studies failed to elucidate the common genetic variation underlying this phenotype, which could emerge years after the completion of treatment. We performed a genome-wide association study on a Spanish cohort of 741 individuals with prostate cancer treated with external beam radiotherapy (EBRT). The replication cohorts consisted of 633 cases from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 42 publications
0
96
0
Order By: Relevance
“…[23][24][25][26][27][28] None of the genetic variants identified in this study emerged as risk factors in these prior investigations.…”
Section: Genetic Risk Factors For Radiation Vasculopathymentioning
confidence: 60%
“…[23][24][25][26][27][28] None of the genetic variants identified in this study emerged as risk factors in these prior investigations.…”
Section: Genetic Risk Factors For Radiation Vasculopathymentioning
confidence: 60%
“…With surgery and chemotherapy, radiation therapy is also one of the highly effective treatments and plays a prominent role in cancer prognosis [78,79]. Studies have identified biomarkers which showed some predictive of patient response to drug treatment [80].…”
Section: Proteogenomic Based Biomarkers To Monitor Radiation Therapy mentioning
confidence: 99%
“…Radiation induced late toxicity can considerably limit treatment frequency and it has negative impact in tumor control. Moreover, late radiation-induced toxicity negatively impact the quality of life of survivors [79]. It is clinically well established that some of the patients are sensitive to ionizing radiations which may trigger radiation-induced toxicities.…”
Section: Proteogenomic Based Biomarkers To Monitor Radiation Therapy mentioning
confidence: 99%
“…Directly demonstrating a genetic factor contributing to non-syndromic human radiosensitivity, a large genomewide association study with requisite power demonstrated a novel candidate radiosensitivity gene, TANC1, within a defined genomic region in a RS prostate cancer cohort compared to control (14). Mutations in this gene were associated with late RT toxicity.…”
Section: Introductionmentioning
confidence: 99%